ANALISIS PERLINDUNGAN HUKUM ISLAM TERHADAP PEMBERIAN MAHAR PERNIKAHAN BERUPA SAHAM - Fadlillah, Ihsan; Amin Ash Shabah, Musyaffa; Wastoni, Oni (MASLAHAH (Jurnal Hukum Islam dan Perbankan Syariah), 2024)
Dowry is an essential aspect of marriage. Scholars agree that while there is no fixed amount for a dowry, it must be beneficial and valuable, reflecting sincerity and affection. This study is normative research using descriptive-analytical data analysis. It explains that dowry in the form of shares is permissible in Islam as long as it does not harm anyone, is agreed upon by both parties and benefits the wife. The shares given must have clear contracts and be within the realm of Sharia-compliant business, even though they cannot be physically displayed, and there must be original proof of ownership of the shares. Legal protection regarding shares is based on the DSN MUI fatwa No. 40 of 2003 article 2, which states: Article 2 (a) The capital market and all its mechanisms, particularly concerning issuers, types of securities traded, and trading mechanisms, are considered compliant with Sharia principles if they fulfil Sharia principles. (b) All securities comply with Sharia principles if they have obtained a Sharia compliance statement.